The Role of Teacher in Science Learning through Multiple Intelligences in Sekolah Peradaban Cilegon - Nulhakim, Lukman; Wibawa, Basuki; Erwin, Tuti Nuriah; Syahrial, Zulfiati (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to see the role of teacher in science learning through Multiple Intelligences in Sekolah Peradaban Cilegon. This study describes the implementation of learning in Sekolah Peradaban Cilegon from the planning of learning, the implementation of learning and the assessment of learning. The method in this research is quantitative descriptive method. The research was carried out in Sekolah Peradaban Cilegon, with the subject of research is the 4th grade student and the amount are 14 students. The instrument used in this study is the observation sheet. The results of the study showed that the implementation of learning planning showed an average score of 4.66 or 93.33% which was in very suitable criteria, the implementation of learning showed an average score of 4.76 or 95.29% which was in very suitable criteria, and for the assesment of learning showed average scores of 4.5 or 90% is very suitable criteria. Based on the results of the study, it can be concluded that the role of teacher in science learning through Multiple Intelligences in Sekolah Peradaban Cilegon is in accordance with the criteria for learning that encourages Multiple Intelligences in Sekolah Peradaban Cilegon